ORGANIZACJA WSPARCIA INFORMACYJNEGO DLA WOJSKOWEGO BEZPIECZEŃSTWA PAŃSTWA - ROMANCHENKO Igor; HVOZD Victor (2018)
Global trends show that information factors in politics are strategic, playing an increasingly important role in shaping and implementing the military policy of states. In this regard, relevant is the issue of scientific recognition and understanding of the key role of information support to the military security of a state. The article gives the points of view on the main aspects of organizing a system of information support to the military security of a state and requirements to such a system.